Validity and reliability of the Fatigue Severity Scale in Finnish multiple sclerosis patients - Eija Rosti-Otajärvi; Päivi Hämäläinen; Anna Wiksten; Tanja Hakkarainen; Juhani Ruutiainen (Wiley Open Access, 2022)
Background
Fatigue is one of the most debilitating symptoms in multiple sclerosis (MS) considerably interfering with patients’ daily functioning. Both researchers and clinicians need psychometrically robust methods to evaluate fatigue in MS.
Objectives
The objective of this study was (i) to evaluate the psychometric properties of the Finnish version of the Fatigue Severity Scale (FSS) and (ii) to describe the results among patients with MS.
Methods
In total, 553 patients with MS (mean age, 53.8 years; standard deviation [SD], 11.4; 79% women: mean patient-defined disease severity, Expanded Disability Status Scale [EDSS] 4.0, SD, 2.5) completed the self-administered questionnaires including the FSS. A standard procedure was used for the translation of the FSS.
Results
The mean (SD) score for the FSS was 4.5 (1.7); in 65% of the patients, the score was ≥4.0. The data quality of the FSS was excellent, with 99.6% of computable scale scores. Floor and ceiling effects were minimal. The FSS showed high internal consistency (Cronbach's alpha, 0.95). Unidimensionality was supported based on confirmatory factor analysis with the comparative fit index being 0.94. The FSS showed moderate/high correlations with the perceived burden of the disease, quality of life and disease severity, whereas, age or gender did not have a significant effect on the FSS score.
Conclusions
The Finnish version of the FSS showed satisfactory reliability and validity and thus can be regarded as a feasible measure of self-reported fatigue.